1969
DOI: 10.1515/znb-1969-1220
|View full text |Cite
|
Sign up to set email alerts
|

Hemmung des Wachstums von Pilzen und Bakterien durch das Hautdrüsensekret von Salamandra maculosa

Abstract: G e r h a r d H a b e r m e h l u n d H a n s -J ü r g e n P r e u s s e r Material und MethodenAls Testsubstanz wurde gefriergetrocknetes Sala mander-Rohsekret in Phosphat-Puffer vom pH 6,0 -einem für das Pilzwachstum günstigen Bereich -und vom pH 7,4 -dem pH-Wert des frisch gewonnenen Rohsekrets -gelöst. Kristallisierte Samandarin-Base, die nach einem früher beschriebenen Verfahren 2' 3 aus Rohsekret gewonnen wurde, diente uns nach Suspen sion in Phosphat-Puffer vom pH 7,4 als weitere Test substanz. Die Prü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Nine members of this class of alkaloids were previously described; the three SAMs samandarine, samandarone and O-acetylsamandarine are considered to be the main alkaloids in salamander skin poison (Vences et al, 2014;Sanchez et al, 2018b). Although SAMs might provide an antimicrobial defence (Habermehl & Preusser, 1969, 1970Preusser et al, 1975), they are mostly known for their physiology-disrupting capacities in vertebrates; acting as convulsive neurotoxins that can cause lethal intoxication even in large mammals such as dogs (Erjavec, Lukanc & Zel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nine members of this class of alkaloids were previously described; the three SAMs samandarine, samandarone and O-acetylsamandarine are considered to be the main alkaloids in salamander skin poison (Vences et al, 2014;Sanchez et al, 2018b). Although SAMs might provide an antimicrobial defence (Habermehl & Preusser, 1969, 1970Preusser et al, 1975), they are mostly known for their physiology-disrupting capacities in vertebrates; acting as convulsive neurotoxins that can cause lethal intoxication even in large mammals such as dogs (Erjavec, Lukanc & Zel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2018) have been suggested to play a major role in amphibian defenses against pathogens. In Salamandra sp., this is supported by the fact that crude skin secretions show higher antimicrobial activity than individual SAMs (Habermehl & Preusser 1969; Preusser et al . 1975), and that denaturation of proteins in the skin secretions drastically reduces its effectiveness in killing chytrid spores (Smith et al .…”
Section: Discussionmentioning
confidence: 90%
“…2018; Smith et al . 2018), and it was demonstrated that S. salamandra individuals completely deprived of their skin secretions succumb to infections within weeks, unless kept in a sterile environment (Habermehl & Preusser 1969). Older literature refers to the compound samandarine as the most potent neurotoxin among the SAMs (Geßner & Esser 1935a; Kellaway 1939; but see Becker 1986; Lüddecke et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 The granular glands can synthesize a wide range of chemical compounds, which provide protection against bacterial and fungal infection as well as predators. 27 Salamanders ( Salamandra salamandra ) deprived of their skin gland secretions soon died from a variety of infections unless kept under sterile conditions, 28 indicating that the glands were important to maintain the skin immune system. Studies have also shown that there were 155 proteins in the skin mucus of Chinese giant salamander and these proteins participated in varieties of physiological activities, including defense, immune response, wound healing, respiration.…”
Section: Discussionmentioning
confidence: 99%